Beyond the Bellows: A Critical Review of Free Reed Instrument Research, Gaps, and Future Innovations (American Journal of Arts and Human Science, 2025)
This paper presents a structured and technical review of free reed instrument research, focusing on four critical aspects: sound production mechanisms, structural analysis, material characterization, and vibration analysis. Through a detailed classification of over 100 studies, we identify prevailing trends, methodological approaches, and underexplored areas. A significant portion of the literature focuses on Western instruments like the accordion and harmonica, while traditional Asian instruments such as the sheng and khaen remain critically under-researched. Methodologically, the field is dominated by experimental studies and finite element modeling (FEM), with limited integration of computational advancements such as machine learning or artificial intelligence (AI). Furthermore, structural and material research often overlooks eco-friendly or sustainable alternatives, suggesting a gap in environmentally conscious design. This review advocates for a more interdisciplinary approach, combining acoustics, structural dynamics, and material science with global perspectives on lesser-known instruments. Emerging trends, such as digital augmentation and AI-driven sound optimization, present promising avenues for future exploration. Additionally, the review underscores the need for sustainable design in instrument construction, as the field remains focused on traditional materials. By identifying key gaps and proposing future directions, this review provides a roadmap for advancing research in free reed instruments through innovation, sustainability, and a more inclusive global outlook.